2021
DOI: 10.1177/10778012211022780
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Nature of Violence Against Women Experiencing Homelessness: A Quantitative Study

Abstract: Individuals experiencing homelessness—an extreme form of social exclusion—have considerably higher risk of being victims of violence than the general population. We analyze the episodes of violence suffered by 504 individuals experiencing homelessness in Spain, as well as the differences between men and women. The results indicate high levels of violence and suggest that gender (specifically, being a woman) is the primary factor driving exposure to violence among this group. Highlighting the reality of women e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 67 publications
0
9
0
6
Order By: Relevance
“…Understanding this delayed effect of DVHF will require further analyses and may become clearer when examining additional time points. Prior research has linked homelessness to increased risk of abuse (e.g., Calvo et al, 2021 ; Gilroy et al, 2016 ), so it may be that housing stability is a precursor to safety. The difference may also relate to the fact that more of the participants who had received DVHF continued to be receiving support between the 6 and 12-month time points.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding this delayed effect of DVHF will require further analyses and may become clearer when examining additional time points. Prior research has linked homelessness to increased risk of abuse (e.g., Calvo et al, 2021 ; Gilroy et al, 2016 ), so it may be that housing stability is a precursor to safety. The difference may also relate to the fact that more of the participants who had received DVHF continued to be receiving support between the 6 and 12-month time points.…”
Section: Discussionmentioning
confidence: 99%
“…Concretamente, en España, el 51% de las PsSH afirman haber sido víctimas de algún tipo de delito o agresión desde que están en esta situación (Instituto Nacional de Estadística, 2012). De la misma forma, Calvo et al (2021) hallaron que el 76.2 % de las PsSH participantes de su estudio habían sido víctimas de, al menos, un episodio de violencia en el último año. Muñoz et al (2018) identificaron que el 55.1% de las personas que pernoctaban en la calle habían sido víctimas de una agresión desde que se encontraban afectadas por el SH.…”
Section: Aporofobia Y Violencia En Psshunclassified
“…En este sentido, la tasa de victimización encontrada en este estudio (44.7%), aunque es inferior a la hallada en otros estudios previos (Barrett & Christopher, 2005;Calvo et al, 2021;Instituto Nacional de Estadística, 2012;Meinbresse et al, 2014;RAIS Fundación, 2015), se sitúa en línea con las últimas estimaciones que señalan que la violencia afecta entre el 27% y el 52 % de las PsSH (Nilsson et al, 2020). Aunque España no dispone de encuestas de victimización a nivel estatal (Sobrino Garcés et al, 2021) y hay que comparar los datos con cautela, algunos trabajos sitúan la tasa de victimización para la población general entre el 17% (Díez-Ripollés y García-España, 2009) y el 33% (Centro de Investigaciones Sociológicas, 2015).…”
Section: Discusión Y Conclusionesunclassified
See 1 more Smart Citation
“…Some authors investigating gender differences related to the experience of homelessness found that men tend to report more substance abuse and legal problems, while women experience more sexual, physical, and psychological abuse, violence by a partner (Calvo et al, 2021;Rodriguez-Moreno et al, 2021), and are more at risk for trauma and victimization (Nyamathi, Leake, & Gelberg, 2000). This may be the reason why scholars reported that women, compared to men in the same condition, show more psychological distress and lower self-esteem (Calvo et al, 2021;de Vet et al, 2019). Moreover, social isolation-one of the main sociocultural factors that contribute to their vulnerability-is marked by a gender-related stigma (Markowitz & Syverson, 2021).…”
Section: Women Experiencing Homelessnessmentioning
confidence: 99%